CORONA EFFECTS AND OHMIC COUPLING ON AC CIRCUITS ON HYBRID OVERHEAD LINES CASE STUDY: AUSTRIAN 420 kV and INDONESIAN 500 kV TOWER SETUPS - Rizki Pratama, Andhika
Converting an AC circuit of an existing multi circuit overhead line (OHL) to DC is a promising solutions to increase the OHL’s transmission capacity. Such OHLs are usually referred to as “hybrid OHL”. Because of the small distances, electromagnetic coupling occurs between the AC and DC circuits. This influences conductor surface gradients, which in return affects corona effects such as audible noise (AN). In this first part of this contribution, simulations regarding capacitive and ohmic coupling affecting the surface gradients of the AC circuits of a fictive Indonesian 500 kV and Austrian 420 kV OHL are presented. The second part deals with partial discharge measurement performed on a small scale laboratory setup at Graz University of Technology to observe the hybrid influences on AC circuits (capacitive coupling and ohmic coupling). The third part deals with audible noise experiments, which were carried out in the High Voltage Laboratory of Graz University of Technology. The aim of the experiments was to investigate the audible noise behavior of AC lines under hybrid condition (DC offset). The discharge process on the conductor surface was monitored using sound level meters and a partial discharge (PD) measurement tool according to IEC 60270. Additionally, the performance of noise reducing surface treatments under hybrid conditions was investigated. The gathered results clearly show that an AC line’s corona behavior worsens substantially under DC influence. This does not only apply to the overall audible noise sound pressure level but also to the AN tonal components. Surface treatments, however, retain their noise reducing effects even under hybrid influences.